Learning Strategies in Aqidah Akhlak to Foster Self-Confidence and Overcome Insecurity Among Students of MTs Darul Ulum Panaragan Jaya in The Era of Social Media - Salma Hanifatus Syafa; M. Sayyidul Abrori; Kholida Nur (Journal of Research in Islamic Education, 2026)
The purpose of this study is to identify appropriate Aqidah Akhlak learning strategies in fostering self-confidence and overcoming insecurity among students of MTs Darul Ulum Panaragan Jaya in the era of social media. The current digital era has brought changes in patterns of social interaction, fear of missing out (FOMO), low self-esteem, identity formation, and students’ moral development. This study employed a qualitative research method using data collection techniques in the form of interviews, observations, and documentation. The data analysis techniques included data reduction, data display, and conclusion drawing. The results indicate that many students experience low self-confidence due to the influence of social media. The Aqidah Akhlak learning strategies implemented through inquiry-based learning, habituation of positive moral values, and reflective discussions were able to help students enhance their self-confidence and reduce feelings of insecurity. The conclusion of this study emphasizes that Aqidah Akhlak learning plays an important role as a means of character development and mental strengthening for students amid the challenges of the social media era.